Effect of optimized thrombus aspiration on myocardial perfusion and prognosis in acute ST-segment elevation myocardial infarction patients with primary percutaneous coronary intervention - Xu, Boning; Zhang, Chunxin; Wei, Wei; Zhan, Yun; Yang, Mingguo; Wang, Yanjun; Zhao, Jiajian; Lin, Guiyang; zhang, Wen-wen; Huo, Xing; Shi, Bin; Fan, Ling (Frontiers in Cardiovascular Medicine, 2023)
Objective:To investigate the impact of optimized thrombus aspiration on myocardial perfusion,prognosis,and safety in patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention(primary PCI).Methods:A total of 129 patients with STEMI were randomly allocated into control group (Subgroup A and B) and experimental group(Subgroup C and D).Control group received percutaneous transluminal coronary angioplasty (PTCA),thrombus aspiration and primary PCI. experimental group received optimized thrombus aspiration and primary PCI.The number of thrombus aspiration was less than 4 times in Subgroup A and C.The number of thrombus aspiration was performed more than 4 times in Subgroups B and D.The classification of thrombi extracted,the TIMI flow grade,the incidence of no-reflow and slow flow, cTFC,TPI and CK-MB at 12h and 24h after stenting,ST segment resolution of ECG after stenting,NT-proBNP,LVEFat 24 hours,30 days and 180 days after stenting were compared between groups.The incidence of intraoperative and postoperative bleeding complications, stroke events and major cardiovascular events (MACE) were recorded and compared between groups.Results:The classification of thrombi extracted in the experimental group was higher than that in the control group.The TIMI flow grade of the experimental group was better than the control group after thrombus aspiration.After stenting,the advantage still existed,but the difference was not statistically significant.On cTFC,the experimental group was lower than